2011
DOI: 10.1038/hr.2011.152
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the second derivative of the finger photoplethysmogram indices and hemodynamic parameters to anesthesia induction

Abstract: The finger photoplethysmogram (PTG) is a non-invasive method for pulse-wave analysis. The second derivative wave of the PTG (SDPTG) enables evaluation of atherosclerosis and cardiovascular aging. Responses of SDPTG indices and hemodynamic parameters to anesthesia induction are unknown. A total of 42 patients aged X40 years, who may have had atherosclerotic change, and who underwent elective oral surgery, were analyzed. Patients were divided into sevoflurane (S group; N¼22) and sevoflurane with remifentanil (R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Remifentanil is a potent, ultra short-acting μ-opioid analgesic that stimulates cardiac parasympathetic nerves and decreases peripheral vascular resistance 25) . In our previous study, elevation of the b/a (an increased vascular response to blood ejection from the left ventricle) and reduction of the d/a (sympathetically-mediated peripheral vasoconstriction) occurred in the absence of remifentanil; however, this finding was not observed in the presence of remifentanil during the induction of anesthesia 24) . We consider that direct laryngoscopy and tracheal intubation stimulate the cardiac sympathetic activity, thus resulting in an increased heart rate, stroke volume and peripheral vascular resistance, leading to tachycardia and elevated blood pressure.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Remifentanil is a potent, ultra short-acting μ-opioid analgesic that stimulates cardiac parasympathetic nerves and decreases peripheral vascular resistance 25) . In our previous study, elevation of the b/a (an increased vascular response to blood ejection from the left ventricle) and reduction of the d/a (sympathetically-mediated peripheral vasoconstriction) occurred in the absence of remifentanil; however, this finding was not observed in the presence of remifentanil during the induction of anesthesia 24) . We consider that direct laryngoscopy and tracheal intubation stimulate the cardiac sympathetic activity, thus resulting in an increased heart rate, stroke volume and peripheral vascular resistance, leading to tachycardia and elevated blood pressure.…”
Section: Resultsmentioning
confidence: 64%
“…We also found that the DBP was an independent determinant of the d/a, in accordance with previous findings showing that the d/a reflects peripheral vascular resistance 2,15) . In a previous study 24) , we evaluated SDPTG indices (b/a, d/a and the aging index [AGI]) in response to tracheal intubation in patients ≥ 40 years of age in the with age, while the d/a decreased with age, suggesting that stiffness of large arteries increases, while peripheral vascular resistance or the left ventricular afterload increases with age. The c/a decreases with age, and the HF has also been reported to decrease with age 16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…20 The rate of pressure increase is also related to central arterial pressure. 21,22 The d/a index is associated with the reflected wave component of the aortic arterial pressure; then, the d/a index is an indirect clue of arterial stiffness. 19 Consequently, the d/a index reflects the functional properties of peripheral circulation and is also related to peripheral vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…They defined notable points of the curve which facilitate understanding of the pressure wave. Since then, several research groups have related the height of the b, c, and d waves to the a-wave to create measures that can index vascular pathologies (vascular aging, hypertension, arterial stiffness) and predict cardiovascular endpoints [14,28,41,42]. Among these points, c and d points are particularly valuable, as they are supposed to hold information about wave reflection [14], and the parameters derived from them provide information about arterial stiffening [14,35].…”
Section: Discussionmentioning
confidence: 99%